2018
DOI: 10.1177/1475725718766280
|View full text |Cite
|
Sign up to set email alerts
|

Holding the Baby: Using the Leiden Infant Simulator Sensitivity Assessment to Examine Attachment Theory’s Sensitivity Hypothesis

Abstract: Some students taking infant development classes have limited, direct experience of interacting with infants. This paper reports on a pilot of an innovative, research-informed workshop that provides hands-on experience through the use of infant simulators. The workshop adapted the Leiden Infant Sensitivity Simulator Assessment, which uses the RealCare Baby ß infant simulator, to examine attachment theory's sensitivity hypothesis. Students' ratings indicated that an infant simulator activity was helpful in under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Both cohorts saw that the simulators not only complemented traditional teaching and learning methods but extended their knowledge and understanding around the long-term impact, as they commented that they would be able to remember these effects in the future. Several of Julal's (2018) students similarly commented that the interactive workshop helped them clarify their understanding of the concepts being taught and the experience made the information more memorable than just reading about the effects. In addition, both Julal (2018) and Symons and Smith (2014) similarly found that the use of simulators (whether neonate simulators or a VRT programme respectively) improved psychological engagement and critical thinking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both cohorts saw that the simulators not only complemented traditional teaching and learning methods but extended their knowledge and understanding around the long-term impact, as they commented that they would be able to remember these effects in the future. Several of Julal's (2018) students similarly commented that the interactive workshop helped them clarify their understanding of the concepts being taught and the experience made the information more memorable than just reading about the effects. In addition, both Julal (2018) and Symons and Smith (2014) similarly found that the use of simulators (whether neonate simulators or a VRT programme respectively) improved psychological engagement and critical thinking.…”
Section: Discussionmentioning
confidence: 99%
“…Several of Julal's (2018) students similarly commented that the interactive workshop helped them clarify their understanding of the concepts being taught and the experience made the information more memorable than just reading about the effects. In addition, both Julal (2018) and Symons and Smith (2014) similarly found that the use of simulators (whether neonate simulators or a VRT programme respectively) improved psychological engagement and critical thinking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Efficacy outcome studies on infant simulator-based programmes found it positively discouraged teenagers from engaging in unprotected sexual activity by creating simulated classroom experiences that emphasize the adverse consequences of such behaviour (Kralewski and Stevens-Simon, 2000). Research has shown that interaction with the virtual baby dolls provides a creative learning environment for pupils when incorporated into teaching on sexual health as part of creative pedagogy (Gibbons, 2001;Aldrich, 2003;Issenberg et al, 2005) and effectively teaches pupils about the infant-caregiver interaction (Julal, 2018).…”
Section: The Use Of the Virtual Baby Projectmentioning
confidence: 99%